Treatment outcomes and their determinants of IgG4-related ophthalmic disease: a territory-wide cohort study - Lai, Kenneth K H; Li, Emmy Y M; Chan, Regine Y C; Chu, Winnie C W; Cheng, Andy C O; Chan, Karen K W; Chin, Joyce K Y; Kwok, Jeremy S W; Io, Ida Y F; Yip, Nelson K F; Li, Kenneth K W; Chan, Wai Ho; et al. (British journal of ophthalmology, 2023)
BackgroundOral corticosteroid remains the first-line treatment of IgG4-related ophthalmic disease, but steroid-dependence is common and serious. Factors associated with steroid dependence and relapse have to be further explored.Study populationA city-wide, biopsy-proven, Chinese cohort.MethodsRetrospective, masked review of medical records, orbital images and histopathology reports.ResultsThere were 101 patients with at least 24-month follow-up. Up to 82% (82/101) received oral corticosteroid as first-line treatments, and 7 of them received also concomitant steroid-sparing agents (SSA)/biological agents as primary treatment. There was 61% (50/82) of patients required long-term corticosteroid (alone=23, with SSA=27) after 1.9±0.7 (range 1–5) relapses. When compared with the 21% (17/82) of patients who tapered corticosteroid successfully for 24 months, steroid dependence was associated with elevated baseline serum IgG4 level (94% vs 65%, p<0.01) and Mikulicz syndrome (46% vs 18%, p<0.05). Up to 13% (11/82) of patients tolerated residual disease after tapering off corticosteroid. There was 17% (17/101) of patients did not require any medications after biopsies. They were more likely to have debulking surgeries (71% vs 40%, p<0.05), discrete orbital lesions (65% vs 26%, p<0.05), normal baseline serum IgG4 level (24% vs 6%, p<0.05) and no Mikulicz syndrome (94% vs 61%, p<0.05).ConclusionIn this cohort, 60% of patients required long-term maintenance oral corticosteroid. Elevated pretreatment serum IgG4 level and Mikulicz syndrome were associated with steroid dependence. Debulking surgery is an alternative for a subgroup of patients with discrete orbital lesions, normal baseline IgG4 level and no Mikulicz syndrome.